Aesthetic Analysis Of English Embroidery On Modification Of Tulang Bawang Traditional - Safitri, Juliana (Corak, 2022)
The traditional clothing of the Tulang Bawang province of Lampung is thick with eastern traditions with closed clothing models and upholds the value of modesty. The traditional clothes of Tulang Bawang are eaten as a symbol to show the greatness of Lampung culture. The traditional clothing of Tulang Bawang must be preserved so that it remains in demand by the public and can be introduced more widely. One way is to make modifications. The use of decoration on clothing is also very influential and will add value to dress. The application of English embroidery as a decoration on clothing was chosen because English embroidery has unique characteristics that distinguish English embroidery and other embroideries. The use of English embroidery on the dress will display an exclusive impression on the clothing and will undoubtedly support the realization of the modification of the traditional Tulang Bawang clothing that is used for party occasions. This study aims to discuss the aesthetics of applying English embroidery to the improvement of the traditional clothes of Tulang Bawang. The research method was carried out with a qualitative descriptive method. The results of the author's research on fashion work with the theory put forward by Darsono Sony Kartika (2007), the fashion works have met the quality of aesthetic values. The aesthetic value of clothing can be seen from the elements, which include: unity, harmony, symmetry, balance, and contrast.